DEVELOPMENT AND STUDY OF THE CHARACTERISTICS OF OPHTHALMIC GELS BASED ON CARBOMER ACRYPOL 974P AND CADPOL 980 - Y. M. Domnina; S. A. Kedik; V. V. Suslov; E. A. Shnyak (Разработка и регистрация лекарственных средств, 2019)
The work is devoted to the development of novel ophthalmic drug prolonged action in the treatment of cataract of different genesis, degeneration and corneal injury. The results showed the possibility of creating an ophthalmic gel based on carbomers with the addition taurine. The resulting preparation was studied on the basic parameters that demand for ophthalmic dosage forms.